2022
DOI: 10.28982/josam.1055862
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic nutritional index is associated with mortality of patients in intensive care unit

Abstract: Background/Aim: It has been reported that the prognostic nutritional index (PNI) is ), an immunonutritional index, associated with poor prognosis, especially in cardiovascular and malignant diseases. However, the clinical significance of PNI in intensive care (ICU) patients remains unclear. In this study, we aimed to measure the predictive value of the PNI in predicting mortality in patients hospitalized in the ICU. Methods: A total of 80 patients hospitalized in the internal medicine ICU of our hospital betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…However, both the GNRI and PNI scores were reported as independent risk factors for short-term mortality in earlier studies. [24,33] In our study, HALP score showed no significant relationship with ICU mortality (P = .78), which is inconsistent with earlier studies reporting that HALP is good at predicting mortality with either high or low sensitivity and specificity in geriatric patients with acute ischemic stroke. [29,34] In brief, the key finding of our study was the presence of an association between the indices used in the study, except for HALP score, ICU LOS, and ICU mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, both the GNRI and PNI scores were reported as independent risk factors for short-term mortality in earlier studies. [24,33] In our study, HALP score showed no significant relationship with ICU mortality (P = .78), which is inconsistent with earlier studies reporting that HALP is good at predicting mortality with either high or low sensitivity and specificity in geriatric patients with acute ischemic stroke. [29,34] In brief, the key finding of our study was the presence of an association between the indices used in the study, except for HALP score, ICU LOS, and ICU mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…The median scores of APACHE-II, SOFA, and mNUTRIC were significantly higher and the mean scores of PNI and GNRI were significantly lower in the non-survivor group (P > .05 for all) and were consistent with those reported in several studies on different patient populations. [22][23][24]27] In the present study, the HALP score did not differ between the survivor and non-survivor groups (P = .29), which was in line with the results of another study by Türkiye (P = .380). [28] However, in another study, the HALP score was significantly lower in the non-survivor group than in the survivor group of patients with ischemic stroke (P = .00).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations